Water oxidation catalyzed by molecular di- and nonanuclear Fe complexes: importance of a proper ligand framework. Issue 34 (6th June 2016) - Das, Biswanath; Lee, Bao-Lin; Karlsson, Erik A.; Åkermark, Torbjörn; Shatskiy, Andrey; Demeshko, Serhiy; Liao, Rong-Zhen; Laine, Tanja M.; Haukka, Matti; Zeglio, Erica; Abdel-Magied, Ahmed F.; Siegbahn, Per E. M.; et al.
Abstract : The synthesis of two molecular iron complexes, a dinuclear iron(iii, iii ) complex and a nonanuclear iron complex, and their use as water oxidation catalysts is described. Abstract : The synthesis of two molecular iron complexes, a dinuclear iron(iii, iii ) complex and a nonanuclear iron complex, based on the dinucleating ligand 2, 2′-(2-hydroxy-5-methyl-1, 3-phenylene)bis(1 H -benzo[ d ]imidazole-4-carboxylic acid) is described. The two iron complexes were found to drive the oxidation of water by the one-electron oxidant [Ru(bpy)3 ] 3+ .